CORPO TRANSGRESSOR FEMININO: A ARTE ROMPENDO ESTIGMAS NUM DIÁLOGO DE ENFRENTAMENTO DA VIOLÊNCIA DOMÉSTICA PRATICADA CONTRA A MULHER - Casoli, Rosemery (2020)
This dissertation is the result of a research that develops the conceptualization of the term female transgressor body from the investigative study of the construction of domestic violence practiced against women and the use of art as a possibility of p